Diabetes and Heart Failure - Alarco, Walter (2020)
Diabetes Mellitus (DM) is a chronic non-communicable cardio-metabolic disease that causes macro-vascular complications such as atherosclerosis, coronary disease and heart failure (HF). There is a bidi- rectional relationship between HF and DM, HF being the second most frequent initial  cardiovascular event in patients with diabetes. It may even be the first cardiovascular complication, before acute my- ocardial infarction.DM can lead to HF through mechanisms mediated by atherosclerosis and non mediated by it. In the first case, cholesterol is deposited in coronary arteries, favored by the presence of other risk factors. In the second case, the myocardium is directly affected leading to structural and functional changes through non-atherogenic mechanisms (called Diabetic Cardiomyopathy).The treatment of HF with reduced ejection fraction in the diabetic patient does not differ from that of the non-diabetic population, the triple neurohumoral block must be achieved. In the case of patients with HF with ejection fraction preserved to date, we do not have specific therapy to reduce cardiovas- cular morbidity and mortality. In the diabetes treatment of the patient with HF, sodium-glucose type 2 cotransporter inhibitors (SGLT2i) clearly stand out. In addition to their glucosuric and natriuretic effect, they have pleiotropic effects that produce metabolic, hemodynamic and cellular viability effects preventing apoptosis and cell death. Finally, the clinical benefits of SGLT2 inhibitors in HF go beyond glycemic control, as demon- strated by the DAPA-HF study; initiating a new era in the treatment of patients with HF with reduced ejection fraction.